Outcome of Management of Central Serous Chorioretinopathy (Community Based Medical Journal, 2025)
This case series study on central serous chorioretinopathy (CSCR) was conducted, from April 2022 to October 2022, to assess the efficacy of laser photocoagulation and AntiVEGF in central serous chorioretinopathy. This study included all patients presented with CSCR in Bangladesh Eye Hospital, Uttara, Dhaka, a tertiary specialized private eye hospital in Bangladesh. These cases were diagnosed clinically and confirmed by fundus fluorescence angiogram and optical coherence tomography. The main features evaluated were corrected visual acuity, associated findings and complications after laser or AntiVEGF injection, if any.  Other data included were age, gender, laterality of eyes, risk factors, and types of leaking. Twenty-eight cases were selected after thorough evaluation; focal laser was performed in 16 indicated cases, and intravitreal AntiVEGF (Bevacizumab) were given 4 cases of subfoveal leak central serous chorioretinopathy after 4-month observation. Post-intervention follow-up schedules were one week, one month and three months. Out of 28 cases, 7 were central serous chorioretinopathy with a sub-foveal leak in the angiogram. Among those, 10 cases were presented with central serous chorioretinopathy with pigment epithelial detachment. After three months of follow-up, subretinal fluid disappeared in 14 cases out of 16 cases of laser. Spontaneous resolution occurred in 7 cases. One patient was presented with RPE tracking. Age limits were extended from 22 to 48 years, and most were in the third decade. Central serous chorioretinopathy is most commonly present without any specific cause. Due to professional demand, most causes need intervention, which will result in fruitful visual acuity improvement with reduced subjective contrast.  CBMJ 2025 January: Vol. 14 No. 01 P:76-80